Stubborn Exercise Responders-Where to Next? - Leo R. Bell; Tim J. Gabbett; Gregory M. Davis; Matthew P. Wallen; Brendan J. O'Brien (MDPI AG, 2022)
There is a wide variance in the magnitude of physiological adaptations after resistance or endurance training. The incidence of "non" or "poor" responders to training has been reported to represent as high as 40% of the project's sample. However, the incidence of poor responders to training can be ameliorated with manipulation of either the training frequency, intensity, type and duration. Additionally, global non-response to cardio-respiratory fitness training is eliminated when evaluating several health measures beyond just the target variables as at least one or more measure improves. More research is required to determine if altering resistance training variables results in a more favourable response in individuals with an initial poor response to resistance training. Moreover, we recommend abandoning the term "poor" responders, as ultimately the magnitude of change in cardiorespiratory fitness in response to endurance training is similar in "poor" and "high" responders if the training frequency is subsequently increased. Therefore, we propose "stubborn" responders as a more appropriate term. Future research should focus on developing viable physiological and lifestyle screening tests that identify likely stubborn responders to conventional exercise training guidelines before the individual engages with training. Exerkines, DNA damage, metabolomic responses in blood, saliva and breath, gene sequence, gene expression and epigenetics are candidate biomarkers that warrant investigation into their relationship with trainability. Crucially, viable biomarker screening tests should show good construct validity to distinguish between different exercise loads, and possess excellent sensitivity and reliability. Furthermore "red flag" tests of likely poor responders to training should be practical to assess in clinical settings and be affordable and non-invasive. Early identification of stubborn responders would enable optimization of training programs from the onset of training to maintain exercise motivation and optimize the impact on training adaptations and health.